Human relationships in school administration and their effectiveness in achieving psychological compatibility for teachers of intermediate education: field study in the city of Millia’s middle schools, Jijel - Gherraz, Tahar; Laoubi, Younes; Zenkoufi, Fouzia (Journal of Human Sciences, 2022)
The study aimed to identify the degree of middle school principals using the method of human relations in school management and its relationship to the level of psychological compatibility of professors. The study sample consisted of (76) professors who were randomly selected from a research community consisting of 483 in total with a rate of 15.73%. a questionnaire consisting of two measures was used, a measure to determine the degree of usage consisting of (30) items, and a measure to determine the level of psychological compatibility consisting of (23) items, and appropriate statistical methods were used to analyze the data using the statistical analysis program (spss). The results of the study indicated that the degree of managers' use of the human relations method is relatively high at (67.10%), and the psychological compatibility level of teachers is also high reaching (77.63%), and the results as well indicated a positive correlation between the degree of managers using the human relations method in School administration and the level of psychological compatibility of teachers, where the coefficient of correlation was (0.66) at the level of significance (0.01).